2018
DOI: 10.1016/j.btre.2018.e00279
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of Rhizomucor pusillus FCH 5.7, a thermophilic zygomycete involved in plant biomass degradation harbouring putative GH9 endoglucanases

Abstract: HighlightsR. pusillus encodes cellulose-, xylan- and chitin-degrading proteins.Two putative GH9 endoglucanases were identified.Enzyme system of R. pusillus is suited to consume easily accessible sugars.Endoglucanase and xylanase activity detected when the fungus was grown on wheat bran and xylan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…4). These species are not known as strong lignocellulose degraders and their genomes contain only about a half of the number of the CAZymes identified in the lignocellulolytic fungus Thielavia terrestris 28,29 . These fast-growing Mucoraceae are widespread in nature; they are often the first fungi to occupy moist plant debris 30 and are known for their ability to degrade starch, proteins and lipids, which are much less recalcitrant substrates compared to lignocellulose.…”
Section: Resultsmentioning
confidence: 99%
“…4). These species are not known as strong lignocellulose degraders and their genomes contain only about a half of the number of the CAZymes identified in the lignocellulolytic fungus Thielavia terrestris 28,29 . These fast-growing Mucoraceae are widespread in nature; they are often the first fungi to occupy moist plant debris 30 and are known for their ability to degrade starch, proteins and lipids, which are much less recalcitrant substrates compared to lignocellulose.…”
Section: Resultsmentioning
confidence: 99%
“…Thielavia terrestris, (Garcia-Huante et al 2017), Talaromyces thermophilus (Maalej et al 2009), Paecilomyces thermophile (Fan et al 2012), Achaetomium sp. X2-8 (Chadha et al 2019), Rhizomucor pusillus (Hüttner et al 2018), Rasamsonia emersonii, (Martínez et al 2016) T. Leycettanus (Wang et al 2017), Melanocarpus albomyces (Gupta et al 2013) and Aspergillus oryzae LC1 (Bhardwaj et al 2019) were found to be producer of hyper-thermophilic active xylanase. Several alkali stable xylanases were obtained from different fungal strains such as Paenibacillus barcinonensis (Valenzuela et al 2010), Aspergillus fumigatus MA28 (Bajaj and Abbass 2011), Cladosporium oxysporum (Guan et al 2016) and Aspergillus oryzae LC1 (Bhardwaj et al 2019).…”
Section: Fungal Sources Of Xylanasesmentioning
confidence: 99%
“…Different thermophilic fungi such as Thielavia terrestris ( García-Huante et al, 2017 ) , Rhizomucor pusillus ( Hüttner et al, 2018 ) , and Corynascus thermophiles ( van den Brink et al, 2013 ) have been reported as very good sources of thermostable xylanase. It was recently shown that Thielavia terrestris Co3Bag1 produces a highly thermostable xylanase with a molecular weight of 82 kDa.…”
Section: Cellulase and Xylanase Of Thermophilesmentioning
confidence: 99%